Challenges and Solutions in Implementing the Anti-Terrorism Law in Indonesia - Anis Noviya (Journal of Adat Recht, 2025)
Counterterrorism is a top priority for Indonesia's national security, as regulated in Law No. 5 of 2018 on the Eradication of Criminal Acts of Terrorism. Although this law provides a comprehensive legal framework for dealing with terrorism, its implementation in the field faces significant challenges. This study aims to explore the main challenges in the implementation of the Anti-Terrorism Law and identify potential solutions to address these problems. The method used in this study is a qualitative approach, with data collection techniques through in-depth interviews with legal practitioners, analysis of legal and policy documents, and case studies of several terrorism incidents in Indonesia. The results of the study indicate that the main challenges include lack of coordination between institutions, limited resources and training, and issues related to human rights. This study also found that potential solutions include increasing cooperation between institutions, providing better training, and strengthening oversight mechanisms to ensure that law enforcement does not violate basic rights. These findings are expected to provide valuable insights for policymakers and legal practitioners in improving the effectiveness of the implementation of the anti-terrorism law in Indonesia.